Writing and Translation process research: Bridging the gap (Introduction) - Dam-Jensen, Helle; Heine, Carmen (Journal of Writing Research, 2013)
Writing and translation are traditionally addressed as two different objects of study. However, they also share many characteristics - as revealed by the research carried out in the two fields, which often uses the same methods to investigate both areas. In this introduction, it is suggested that writing and translation can be studied as types of text production. Different dimensions of text production are sketched as examples of research topics at the interface between writing and translation. The two articles that follow this introduction explore two such dimensions: competence and profiles.